Microwave aquametry: a growing technology - Khalid, Kaida (Bahagian Komunikasi Korporat, Universiti Putra Malaysia, 2004)
A rapid growth of microwaves system has taken place after the Second World War in the area of telecommunication and navigation in both civilian and military. However, industrial, scientific, medical and domestic applications have developed at a slower pace. By far, the most popular application of microwave power is in microwave oven for domestic and commercial cooking. On the other hand, a greater variety of industrial applications of high microwave power has been demonstrated including applications in various industries such as rubber, food, textiles, plastics, foundry, building materials, paper, pharmaceuticals, cosmetics, and coal. The main advantage of microwave power in processing of materials are increased rate of production, improved product characteristics, uniform processing and controllability of the process. Low-intensity microwaves have found industrial, scientific and medical application in a non-destructive testing and monitoring of material, objects and people. These include microwave aquametry and mechanical parameters monitoring and the first known patent was granted in Sweden in 1945. Microwave methods have also been used in medical diagnosis such as cancer detection and monitoring of respiratory systems. It was only recently that the measurement of dielectric properties has been applied to microwave aquametry for on-line process control in the manufacturing industries. However, the measurement and use of dielectric properties has been a concern of the physical sciences for almost a decade ago. In past years, two Nobel Prizes have been awarded to scientists Debye (1936) and Onsager (1968) for their work involving dielectric theory and the application of Maxwell's electromagnetic theory. The objective of this paper is to expose the growing technology of microwave aquametry and highlight its most interesting and successful applications. In organising and presenting the material, an attempt was made to meet four goals. First to show the dielectric properties of water and moist substances, second the state of the art of microwave aquametry system, third to show the development of microwave sensors and instrumentation for that could benefit our agriculture and manufacturing industries and fourth the current development of microwave aquametry for various applications. This work highlights the findings of research over the past 23 years especially in the application of microwave aquametry in rubber and oil palm industries.